Stressor Response Model for the Spotted Sea Trout, Cynoscion nebulosus - Frank J. Mazzotti; Leonard G. Pearlstine; Tomma Barnes; Stephen A. Bortone; Kevin Chartier; Alicia M. Weinstein; Donald DeAngelis (EDIS)
Circular 1523, a 16-page illustrated circular by Frank J. Mazzotti, Leonard G. Pearlstine, Tomma Barnes, Stephen A. Bortone, Kevin Chartier, Alicia M. Weinstein, and Donald DeAngelis, is one of a suite of Caloosahatchee estuary models which are being considered together for Everglades restoration plan evaluation. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, January 2008.